2009
DOI: 10.1161/strokeaha.109.562660
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Arrival Time and Intravenous t-PA Use in US Academic Medical Centers, 2001–2004

Abstract: Background and Purpose-Prompt care-seeking behavior is a focus of US national public stroke educational campaigns.We determined whether the time between symptom onset and hospital arrival and the receipt of intravenous tissue-type plasminogen activator (IV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 40 publications
3
61
0
Order By: Relevance
“…8,10,21 Previously published evidence suggests that of all the patients who present to the ED with stroke, the proportion arriving within 3 hours from symptom onset is less than 50% and within 4 hours is approximately 55%. 22 It is possible that the increase in tPA use over time reflects a higher proportion of patients presenting within the appropriate treatment window. We did not have reliable data concerning time from symptom onset to ED presentation to test this hypothesis; however, previous work suggests that the proportion of patients arriving within 2 hours has not changed significantly over time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,10,21 Previously published evidence suggests that of all the patients who present to the ED with stroke, the proportion arriving within 3 hours from symptom onset is less than 50% and within 4 hours is approximately 55%. 22 It is possible that the increase in tPA use over time reflects a higher proportion of patients presenting within the appropriate treatment window. We did not have reliable data concerning time from symptom onset to ED presentation to test this hypothesis; however, previous work suggests that the proportion of patients arriving within 2 hours has not changed significantly over time.…”
mentioning
confidence: 99%
“…We did not have reliable data concerning time from symptom onset to ED presentation to test this hypothesis; however, previous work suggests that the proportion of patients arriving within 2 hours has not changed significantly over time. 22 This leads us to believe that temporal trends in arrival time may be playing a small role and the more likely explanation is that clinical decision-making and in-hospital systems are leading to more patients receiving tPA. The observed ethnic difference appears to be driven primarily by differences in the recent years of the project when tPA use was increasing dramatically and more so in NHWs.…”
mentioning
confidence: 99%
“…2,36 A major factor in this low rate of IV-tPA for AIS is delayed presentation: many patients simply do not reach medical attention or are not assessed within the therapeutic window. 4,7,27 Delayed presentation to medical care is a multifactorial issue. Importantly, many patients do not appreciate the seriousness of their symptoms or fail to recognize that they are having a stroke.…”
Section: Mobile Stroke Treatment Unitsmentioning
confidence: 99%
“…14 A study of US academic centers found that although the same percentage of patients presented within 2 hours of stroke symptom onset in 2001 and 2004, the use of IV tPA more than doubled over this time period. 18 Improved system organization at the prehospital and hospital levels as well as greater comfort and experience with use of thrombolytic therapy likely contribute to all of these findings. 11 CSCs did not outperform PSCs with regard to stroke education and antithrombotics by end of hospital day 2, but these results were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%